Prevalence of Lip (Diseases/Disorders/Lesions) among Adult Population Visiting Out-Patient Clinic in Central Punjab. - Asma Shakoor, Amna Ghaffar, Awais Ali, Aaliya Saeed, Aamina Sagheer, Javed Iqbal (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To find out the prevalence of various commonly occurring lip anomalies like lip fissures, angular chielitis, lip pits and allergic cheilitis in patients visiting out-patient clinic in central Punjab. Methods: This is a prospective observational study conducted at the diagnostics department of Nishter institute of dentistry, Multan from Feb,2022 to December,2022 for a period of 11 months to determine the relative frequency of various lip anomalies in adult population of central Punjab. Six hundred patients were examined with an age range of 25-35 years in a quite comfortable environment using dental mirror, natural light and surgical gauze. The result was analyzed by using chi-square test in SPSS. Results: The prevalence of lip anomalies in 600 patients was 24.3% among male and female patients. These lesions were more prevalent in patients of 25 to 30 years of age (55.47%) compared to 30-35 years of age (44.52%). Among lip lesions, lip fissures were seen in 7.4% cases, lip pits were 2.6%, allergic chielitis was seen 1.8% and patients with angular chielitis were 12.4%. All lesions showed almost equal distribution among male and female patients seen during the study. Practical Implication: Our study was done in central Punjab region. It highlighted the commonly occurring lesions of lip which could affect the aesthetics of the people as well as has important psychological impact on their daily life. Our study showed the prevalence of lesions and also motivated the people to seek possible treatment of the lesions. It helped a lot to educate affected community and encouraged them to improve their conditions. Conclusion: The results of the study are in accordance with some previous studies although they contradict to some other studies as well. This study has also shown that the lip anomalies are slightly more in females as compared to the males although the statistical difference is not significant. Moreover, the age is not related to the lip anomalies. Keywords: Lip anomalies, Lip fissures, angular chielitis, allergic chielitis, lip pits.